Lamellar bimetallic thiolates: synthesis, characterization, and their utilization for the preparation of bimetallic chalcogenide nanocrystals through mechanochemical grinding - Bera, Abhijit; Pathak, Sushil S.; Kotha, Vishal; Prasad, V, Bhagavatula L. (Advanced Materials Interfaces, 2021)
Thiolates of single metal ions are known to exist as lamellar structures in the neat state and some of these metal thiolates can be delaminated into individual molecular sheets simply by adding a nonpolar organic solvent. It is established here that even bimetallic thiolates such as copper-indium thiolate and silver-indium thiolate exist as lamellar sheets. Each of these sheets consists of both metal ions arranged in a random fashion. It is also demonstrated that these bimetallic thiolates can be employed as single source precursors to prepare phase pure bimetallic chalcogenide nanocrystals (NCs) through mechanochemical routes by grinding them with an appropriate chalcogenide source. Notably, these bimetallic chalcogenide NCs, though synthesized in the absence of any solvent, get easily dispersed in nonpolar solvents as their surface is protected by the thiolate molecules released during the grinding process. These ternary NCs display a strong and tunable photoluminescence in the visible to near-infrared region. Based on detailed systematic studies it is concluded that to obtain phase pure bimetallic sulfide/selenide NCs bimetallic thiolates, consisting of both metal ions in each sheet, must be used as single source precursors and physical mixtures of individual thiolates do not afford such phase pure materials.
Keywords: bimetallic chalcogenide nanocrystals; bimetallic thiolate; mechanochemical grinding